SELF-KNOWLEDGE IN THE ALCIBIADES I, THE APOLOGY OF SOCRATES, AND THE THEAETETUS: THE LIMITS OF THE FIRST-PERSON AND THIRD-PERSON PERSPECTIVES - Marcelo D. Boeri (Universum. Revista de Humanidades y Ciencias Sociales, 2017)
Knowledge of oneself is not easy to attain. Plato was aware of this and in this paper we aim to show that he suspected then, like psychologists know now, that one’s introspective capacity to attain knowledge of oneself is very much restricted and that we must rely on the other as a source of such knowledge. We further argue that, for Plato, this knowledge is not easily achieved given not only the shortcomings of the fi rst-person perspective but also the limitations of the third-person one.